2022
DOI: 10.1155/2022/6712625
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally Expressed lncRNAs as Potential Biomarkers for Gastric Cancer Risk: A Diagnostic Meta-Bioinformatics Analysis

Abstract: Background and Aims. Abnormal expression of lncRNAs is relevant to the occurrence and development of gastric cancer (GC), but the significance remains inconclusive. We performed a diagnostic meta-bioinformatics analysis to elucidate the association between lncRNA expression and GC risk. Methods. Published datasets were selected from PubMed, Embase, CNKI, and Web of Science, up to 1st December 2021. The pooled sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The literature has shown that certain lncRNAs (e.g., HULC, H19, LINC00152, and others) can be useful in the diagnosis or prognosis of GC due to their capability to be detected in tissues and plasma samples, also being associated with tumor progression and the clinical status of cancer patients [83]. For instance, this review previously described SNHG6 as a lncRNA with the potential to be a promising prognostic marker in this malignancy, given its correlation with the survival of GC patients [74].…”
Section: Lncrnas As Potential Diagnostic Prognostic and Therapeutic M...mentioning
confidence: 99%
“…The literature has shown that certain lncRNAs (e.g., HULC, H19, LINC00152, and others) can be useful in the diagnosis or prognosis of GC due to their capability to be detected in tissues and plasma samples, also being associated with tumor progression and the clinical status of cancer patients [83]. For instance, this review previously described SNHG6 as a lncRNA with the potential to be a promising prognostic marker in this malignancy, given its correlation with the survival of GC patients [74].…”
Section: Lncrnas As Potential Diagnostic Prognostic and Therapeutic M...mentioning
confidence: 99%
“…In comparison with healthy controls, GC patients had considerably higher expression levels of the lncRNAs PANDAR, FOXD2-AS1, and SMARCC2 plasma. GC patients have higher plasma levels of the lncRNAs AFAP1-AS1 and FEZF1-AS1 than healthy individuals [ 116 ].…”
Section: Introductionmentioning
confidence: 99%